Pronatec: a estratégia do Partido dos Trabalhadores para a inserção no trabalho precário e atendimento das demandas do capitalismo contemporâneo no Brasil - Martins, Iara Saraiva (2015)
The current education model specifically prepares the working class (workers, poor and their children) to work in the technical functions located in the lower and middle levels of the occupational hierarchy of the production system. The inclusion of youth in these forms of training away from the hiking possibilities into the public higher education, and part of a series of actions organized by capitalist management who do not do in isolation. In this dissertation, we verified the specificity of a Public Policy and Educational developed the plan of the Federal Government for the efforts of the Workers Party, and the kind of mobilization to intervene in political issues affecting young workers. From bibliographical and documentary analysis, we seek to understand how the National Program for Access to Technical Education and Employment (Pronatec) is currently configured as one of the main policies with grants from the federal government for training and youth insertion in the precarious world job. Our understanding was conducted initially, watching the tension of PT governments between neoliberal perspectives and neodesenvolvimentista. Neoliberalism is corresponding chronological restructuring process which is established from the 1970s But neoliberalism and productive restructuring not only limited to the same time expressions and is represented in the political and ideological level of the state organization, with developments and implications on the economic level, the redirection process of capital accumulation and its bases. David Harvey divides the periphery of the workforce into two subgroups: the full-time employees that are characterized by low-skilled manual work and routine, such as secretaries or employees of the financial sector. The second sub-group has employees at any given time, temporary, casual employees and "subcontracting personnel and trained with public subsidy" (Harvey cited Antunes, 2011, p. 58). It is for the second subgroup of the periphery of the labor force that target the training courses offered by Pronatec. The discourse and practice neodesenvolvimentista gained amplitude in Brazil through the implementation of projects of the Federal Government in the energy, infrastructure, transportation and water resources. These projects were condensed in 2007 in the Growth Acceleration Program (PAC). The PAC is executed mainly through the action of multinationals to energy exploration. The program has had his works widely held by governments of the PT on the grounds exaltation of the natural wealth of Brazil, as well as producing independent bioenergy sources for the push of a possible national sovereignty. Not surprisingly, job creation policy in the mining sector and energy emerges and qualifications offered by Pronatec for this sector are diverse. It was possible to understand how the Pronatec condenses qualifications that are linked to regional clusters, national and international.